Effect of injectable antibiotics at breeding on reproductive performance - Pollman, D.S.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 116 sows were used in a study to evaluate the effect of penicillin or long-acting oxytetracycline on reproductive performance. Antibiotic injection at breeding time did not improve farrowing rate or litter size. Therefore, these results indicate that it is not cost effective to inject these antibiotics on the day of breeding.
Keywords: Swine; Antibiotics; Reproductive; Performance